New α-Aminophosphonates as Corrosion Inhibitors for Oil and Gas Pipelines Protection - Evgeny Nikitin; Georgy Shumatbaev; Dmitriy Terenzhev; Kirill Sinyashin; Kamila Kazimova (Salehan Institute of Higher Education, 2019)
The problem of corrosion of metal equipment is one of the most actual problems in oil industry. One of the methods to solve this problem is the development of new low-toxic, accessible and effective corrosion inhibitors. For this purpose, we carried out the synthesis of the new α-aminophosphonates based on syntanyl phosphites, formalin and diethanolamine according to the Kabachnik-Fields reaction. The resulting products are characterized by 1H, 31P, 13C NMR, IR and mass spectroscopy methods. The obtained compounds contain a long radical chain of industrial (poly)ethoxylated alcohol residue with different length of the hydroxyethyl fragment, as well as an active center containing O-P-C-N fragment, which impart them inhibitory properties toward corrosion processes. The anticorrosive activity of the new aminophosphonates was studied by gravimetric analysis method. In the article the effect of concentration, time and degree of ethoxylation of the hydrocarbon radical in alpha-aminophosphonates on the protective effect of inhibitors was studies. It was shown that the obtained aminophosphonates exhibit high values of the protective effect of steel in a highly mineralized medium containing 250 g/m3 СО2 and 200 g/m3 Н2S. The high value of the protective effect (82-85 %) at inhibitor concentration of 25 mg/l was found. The maximum protective effect at 50 mg/ml dosage of the inhibitor is 94.3 %, while there is a decrease of the corrosion rate (less than 0.04 mm/year).